Lethal and sublethal effects of neem oil to the predatory mite Proprioseiopsis neotropicus (Acari: Phytoseiidae) - Silva, Amanda C. B.; Teodoro, Adenir V.; Oliveira, Eugênio E.; Maciel, Anilde G. S. (Revista Colombiana de Entomología, 2013)
Lethal and sublethal toxicity of the neem oil Bioneem® to the predatory mite Proprioseiopsis neotropicus (Acari: Phytoseiidae) were evaluated by combining lethal doses (LD) with population growth and biological parameter studies. Dose-mortality bioassays were conducted to estimate the lethal doses of the neem oil to P. neotropicus using probit analyses. Afterwards, the instantaneous rate of increase (ri) was used to evaluate the sublethal effects of the neem oil to P. neotropicus based on reproduction and mortality data. The effects were further assessed by comparing some life history parameters of P. neotropicus exposed to a sublethal dose of neem oil. The dose of neem oil which kills 50% of the population (LD50) of the predatory mite P. neotropicus was 7.5 μl/ cm2. The instantaneous rate of increase of the predatory mite P. neotropicus did not vary with increases of dosages of neem oil. Similarly, the LD25 of the neem oil did not affect biological parameters of the predatory mite. Based on our lethal and sublethal approach we conclude that the neem oil Bioneem® is generally selective to the predatory mite P. neotropicus.